Acumulação de competências tecnológicas e suas implicações para a performance corporativa: um estudo comparativo entre duas empresas da indústria moveleira em Bento Gonçalves - RS - Ben, Fernando (2001)
This dissertation focus the implication of differences in accumulation of technological competences among companies and its reflex on the improvement of indexes of operational, economical and financial performance. This connection has been investigated at D'Itália Móveis Industrial Ltda. and Pozza S.A Industrial Moveleira, both companies of the furniture market located in Bento Gonçalves - RS. Based on a comparative case study of these two companies, this dissertation is based on empiric evidences about how the company has accumulated its technological competences. Such evidences are qualitative and quantitative, and were collected from several sources in the studied companies. The examination of technological competences accumulation is done based on an analytical structure that exists in the literature, that has been adapted to the analysis of the furniture market. The examination of performance improvement is based on a set of indexes used in the furniture industry. Studies about this subject are found in the literature, but the application of these analytic structures in the furniture market is scarce, mainly in brazilian companies. It has been noticed that the company D'Itália has accumulated technological competences on all the three functions analysed, what suggests implications for the improvement of its performance. On the other side, the company Pozza has shown a paralysation on technological competences accumulation during a long time, what brought implications for the reduction of its corporative performance. In this way, the conclusion of this dissertation suggests that the accumulation of technological competences has contributed to explain the differences of performance between both companies. Besides, it explains how both companies have managed (or not) to accumulate their indexes of performance in the long run. Even though this conclusion is not different from other studies formerly done, this conclusion is derivated from a study applied to a kind of industry that still wasn¿t examined in the available literature.